Development of Inquiry-Based Learning Methods With Differentiated - Arifiyani, Happy; Widodo, Joko; Kusumantoro, Kusumantoro (Universitas Negeri Semarang, 2024)
This study aims to create and develop a product in the form of a differentiation-based inquiry learning method on the subject of economic problems in the accounting expertise program at SMK. The purpose of differentiation learning is to provide a learning experience that is in accordance with the level of readiness, interests, and individual learning styles of students. This study adopts the Research and Development (RnD) approach that adopts the 4D (Four-D) development procedure. The data used is factual data that has been implemented so far. This study did not use a trial but FGD ( Focus Group Discussion) by expert practitioners and academics . In addition, this study was also conducted to determine the activeness of students in differentiation learning in economics learning at SMK. This study was conducted at SMK Kudus Regency, namely SMK N 1 Kudus and SMK PGRI 1 Kudus. The results of this study are in the form of a differentiation-based inquiry learning method , the product is equipped with (1) Differentiation-based inquiry learning method; (2) Differentiation-based inquiry learning method guide; (3) Teaching Guide for differentiation-based inquiry learning economics learning that has been developed has been valid (qualified) to be used as a teaching guide for class XI economics learning in the accounting expertise program at SMK. The characteristics of the method developed are inquiry learning methods based on differentiation of economic problem topics. The products developed are teaching guides and design of inquiry learning methods based on differentiation. The results of the FGD showed that an average of 93% was obtained which was categorized as